Race walking gait and its influence on race walking economy in world-class race walkers - Gomez-Ezeiza, J.; Torres-Unda, J.; Tam, N.; Irazusta, J.; Granados, C.; Santos-Concejero, J. (Journal of Sports Sciences, 2019)
Aim: The aim of this study was to determine the relationships between biomechanical parameters of the gait cycle and race walking economy in world-class Olympic race walkers.